A Bibliographic Study on IFRS Adoption Research in Indonesia - Arham, Amardianto; Firmansyah, Amrie; Nor, Aji M. Elvin; Vito, Bernadi (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to map various research results related to the adoption of International Financial Reporting Standards (IFRS) in Indonesia from 2008 to early 2020. Mapping is based on the level of publisher accreditation, research topics, theories used, research methods, research units, the total number of years of analysis, sample size, research variables, and test results. This study uses a qualitative method with a bibliographic approach. The objects used in this study are 92 research results published by SINTA accredited journals (Indonesia Reputable Journals) or Scopus indexed journals. The results show that the majority of publisher accreditation levels were SINTA 2 and SINTA 4, and none has been indexed by Scopus. The most discussed topic of research is the relationship between IFRS and earnings management and value relevance. Most research uses agency theory as the theoretical basis and uses quantitative methods. Research with quantitative methods uses manufacturing companies listed on the IDX as the unit of analysis with a scope of six years of analysis and an average sample size of 69 companies. The majority of quantitative studies use IFRS adoption as an independent variable, earnings management, and value relevance as the dependent variables, and several studies use moderating variables. Mapping the test results on the effect of IFRS adoption on earnings management shows the same number of positive and no effect and only slightly different from the test results that have a negative effect, while the majority of testing results on value relevance indicate a positive effect. Meanwhile, research with qualitative methods mostly uses the type of a literature review approach, and the results of the study still show the pros and cons.